SAT0222 Investigating the Association Between Rho-Kinase 1 (Rock1) Gene Polymorphisms and Systemic Sclerosis. (23rd January 2014) - Pehlivan, Y.; Oztuzcu, S.; Donmez, S.; Alibaz-Oner, F.; Yildirim Cetin, G.; Yolbas, S.; Bozgeyik, I.; Yilmaz, N.; Ozgen, M.; Kisacik, B.; Pamuk, O. N.; Sayarlioglu, M.; et al.
Abstract : Objectives: Systemic sclerosis (SSc, scleroderma) is an inflammatory diseases characterized by vascular abnormalities and fibrosis (1). The role of Rho-kinase in inflammation, in the pathogenesis of vascular structure and fibrosis has been proved with several studies. We aimed to investigate a possible association between ROCK1 gene polymorphisms and SSc patients in a Turkish population. Methods: A total of 284 patients fulfilling the American Collage of Rheumatology criteria on SSc and 284 healthy control subjects with similar age and sex were enrolled to this study. Genomic DNA from the participants was analyzed by a BioMark HD 96.96 dynamic array system (Fluidigm, CA, USA). For calculation of the significance of differences in genotype and allele frequencies, the chi-square test (with Yates' correction) or Fisher's exact test was used. The haplotype analysis was performed by using online software program, SHEsis (http://analysis.bio-x.cn/myAnalysis.php ). Results: There was an increase in GG genotype frequencies (9.4% in SSc vs. 3.2% in control) and decrease in GA genotype frequencies (90.6% in SSc vs. 96.8% in control, P=0.004, OR (95%CI) of the ROCK1 gene rs112108028 polymorphism. CC genotype and C allele frequencies of the rs111874856 polymorphism were markedly low in cases with SSc (CC, 33.7%, C, 33.7%) when compared to control group (CC, 100.0%, C, 100.0%). TT genotype and T allele were not detected in the control group, whereas these frequencies were found to be high in SSc group (TT, 66.3%, T, 66.3%, P<0.0001). AA (97.8%) genotype and A allele (98.9%) of the rs35996865 polymorphism were significantly more common among SSc group than among controls (AA, 93.9%, A, 95.9%). In the haplotype analysis based on these 3 polymorphisms, four haplotypes (ACA, GCA, ATA and GTA) were found to be significantly associated with SSc, and ATA (27.6%) and GTA (36.2%) haplotypes were present only in patients (P<0.0001). Additionally, no marked association was found between rs1045144 polymorphism and SSc. Conclusions: This is the first study to investigate the potential association between ROCK1 gene polymorphisms and SSc. Our data showed that there is a statistically significant association between ROCK1 gene polymorphism and SSc. Moreover, these findings suggest that functional effects of ROCK1 gene can help to understand the pathogenesis of SSc. Acknowledgements: This study has been funded by a project (BAP TF.12.16) from the University of Gaziantep. Disclosure of Interest: None Declared